Molecular modeling and pharmacokinetics studies of sulfamidophosphonate derivatives as potential candidate against Staphylococcus aureus - Olatunde, Abimbola Modupe; Obiyenwa, Kehinde Gabriel; Oladuji, Tofunmi Emmanuel; Latona, Dayo Felix; Oyebamiji, Abel Kolawole; Olatunji, Nathaniel Oladoye; Semire, Banjo (Eclética Química, 2025)
In silico methods were used in this paper to assess the anti-bacterial activity of Sulfamidophosphonate derivatives against Staphylococcus aureus proteins (1XSD and 4WK3) using molecular docking and ADMET analysis. The results showed that binding affinity (ΔG kJ/mol) ranged from –4.1(NAM) to –7.1 kJ/mol (NAL) for 1XSD, and –5.0 (NAE) to –6.7 kJ/mol (NAM) for 4WK3. Therefore, compounds NAH, NAL, NAN, NAI, NAJ, NAK, 5AD and NAM could be more desirable as inhibitors than Penicillin (–6.0 kJ/mol for 1XSD and –5.4 kJ/mol for 4WK3) in the treatment of Staphylococcus aureus; but ADMET profile revealed that compounds NAF, NAI, NAK NAN and 5AC present attractive pharmacokinetic properties. In this study, compounds NAH, NAL, NAI and NAJ exhibited stronger affinities than the standard (penicillin) against BlaI repressor in complex with DNA (PDB ID: 1XSD) suggesting better inhibitory potential than the standard drug.